Improving rates of immunisation in refugee populations in Australia - Abela Mahimbo (Sax Institute, 2024)
Despite an established humanitarian program running for many years, the health needs of refugees resettled in Australia, particularly immunisation, have not been met adequately. Under-immunisation is one of the top health issues for this population. While there is no population-level immunisation coverage data, seroprevalence studies based on small cohorts of refugees show suboptimal immunity to various vaccine-preventable diseases and lower vaccine coverage for this group than the general population. This is compounded by gaps in immunisation policy and service delivery that further perpetuate access issues and may contribute to under-immunisation. This is particularly pertinent against the backdrop of the coronavirus disease 2019 (COVID-19) pandemic, where there have been significant disruptions in the delivery of routine and catch-up immunisations. This paper briefly analyses the status quo and draws on the key policy considerations for enhancing the equitable provision of immunisation for refugees as recommended by the 2019 World Health Organisation technical guidance report to provide a clear, overarching direction for empirical work on immunisation service delivery for refugees in Australia.